High‐Performance MnO2/Al Battery with In Situ Electrochemically Reformed AlxMnO2 Nanosphere Cathode. Issue 9 (1st August 2021) - Pan, Wending; Mao, Jianjun; Wang, Yifei; Zhao, Xiaolong; Leong, Kee Wah; Luo, Shijing; Chen, Yue; Leung, Dennis Y. C.
Abstract: Aqueous Al–ion battery (AAIB) is regarded as a promising candidate for large‐scale energy storage systems due to its high capacity, high safety, and low cost, with MnO2 proved to be a high‐performance cathode. However, the potential commercial application of this type of battery is plagued by the frequent structural collapse of MnO2 . Herein, an in situ, electrochemically reformed, urchin‐like Al x MnO2 cathode is developed for water‐in‐salt electrolyte‐based AAIBs. Benefiting from its unique α‐MnO2 coated Mn2 AlO4 structure, a high Al ion storage capacity is achieved together with a high discharge voltage plateau of 1.9 V by reversible MnO2 electrolysis. Consequently, the battery exhibits a high specific capacity of 285 mAh g –1 and a high energy density of 370 Wh kg –1 at a high current density of 500 mA g –1 . Improved stability with record capacity retention is also obtained at an ultrahigh current density of 5 A g –1 after 500 cycles. Such a high‐capacity and high‐stability Al x MnO2 cathode would pave the way for in situ electrochemical transformation of cathode design and thus boost the practical application of AAIBs. Abstract : Al x MnO2 nanosphere cathode is electrochemically reformed in situ, which consists of the α‐MnO2 nanorod coating layer and inner Mn2 AlO4 nanoflower. The composite structure enables the MnO2 /Al battery a high discharge voltage plateau of 1.9 V and an enhanced discharge capacity for Al ion storage, attributed to reversible MnO2 electrolysis and Al insertion favored Mn2 AlO4, respectively.